Chimpanzee rights : the philosophers' brief /: the philosophers' brief. (2018) - Andrews, Kristin, 1971-; Comstock, Gary L; G.K.D., Crozier; Donaldson, Sue; Fenton, Andrew; John, Tyler M; Johnson, L. Syd M; Jones, Robert C; Kymlicka, Will; Meynell, Letitia; Nobis, Nathan; Pena-Guzman, David; et al.
No abstract available